Early-onset sepsis in very preterm neonates in Australia and New Zealand, 2007–2018. Issue 1 (15th June 2022) - Duggan, Husharn L; Chow, Sharon S W; Austin, Nicola C; Shah, Prakeshkumar S; Lui, Kei; Tan, Kenneth
Abstract : Objective: To evaluate the epidemiology and population trends of early-onset sepsis in very preterm neonates admitted to neonatal intensive care units (NICU) in Australia and New Zealand. Design: Retrospective observational cohort study using a dual-nation registry database. Setting: 29 NICUs that have contributed to the Australian and New Zealand Neonatal Network. Participants: Neonates born at <32 weeks' gestation born between 2007 and 2018 and then admitted to a NICU. Main outcome measures: Microorganism profiles, incidence, mortality and morbidity. Results: Over the 12-year period, 614 early-onset sepsis cases from 43 178 very preterm admissions (14.2/1000 admissions) were identified. The trends of early-onset sepsis incidence remained stable, varying between 9.8 and 19.4/1000 admissions (linear trend, p=0.56). The leading causative organisms were Escherichia coli ( E. coli ) (33.7%) followed by group B Streptococcus ( GBS ) (16.1%). The incidence of E. coli increased between 2007 (3.2/1000 admissions) and 2018 (8.3/1000 admissions; p=0.02). Neonates with E. coli had higher odds of mortality compared with those with GBS (OR=2.8, 95% CI 1.2 to 6.1). Mortality due to GBS decreased over the same period (2007: 0.6/1000 admissions, 2018: 0.0/1000 admissions; p=0.01). Early-onset sepsis tripled the odds of mortality (OR=3.0, 95% CI 2.4 to 3.7) and halved the odds of survival without morbidity (OR=0.5, 95% CI 0.4 to 0.6). Conclusion: Early-onset sepsis remains an important condition among very preterm populations. Furthermore, E. coli is a dominant microorganism of very preterm early-onset sepsis in Australia and New Zealand. Rates of E. coli have been increasing in recent years, while GBS -associated mortality has decreased. Abstract : In a retrospective study from the Australian New Zealand Neonatal Network database, incidence of early onset sepsis in infants less than 32 weeks gestation was stable over 12 years, and incidence of e.coli, the predominant organism, increased.